Animal magic or a bone of contention? An exploration of dog ownership and adaptation in people with post-stroke aphasia. Issue 12 (2nd December 2021) - Coutts, Emma; Cooper, Kay
ABSTRACT: Background: There is extensive literature on the impact of aphasia on human interactions, with findings including family tension and reduced participation affecting the person with aphasia's ability to adapt to life post-stroke. However, research on relationships between people with aphasia and their pets is sparse. Studies in other healthcare fields have found benefits and drawbacks of pet ownership. The presence of a communication disorder adds a unique perspective, with implications for the ability to interact with the animal. Aim: This study explores the experiences that people with aphasia have of dog ownership as they adapt to life post-stroke, from the perspectives of both people with aphasia and close family members or carers. Methods & procedures: Ten semi-structured interviews were conducted with 17 people with aphasia and/or relatives or carers. Thematic analysis was carried out. Outcomes & results: Three major themes were generated. These were: (i) the adaptation of the dog to the person with aphasia; (ii) the adaptation of the person with aphasia to their dog; (iii) experiences of dog-walking interactions. Positive and negative aspects were reported within each theme. Conclusions: The implications of these findings are significant for rehabilitation professionals: just as the person with aphasia needs support in the context of their human relationships and the challenges and opportunities that these present, their relationship with their dog should also be considered.